Staff Members' Professional Agency within the Staff Community and the Education Policies: Supporting Integration in Multicultural and Multilingual School Communities - Eveliina Manninen; Päivi Hökkä; Mirja Tarnanen; Katja Vähäsantanen (MDPI AG, 2022)
In recent decades, increased diversity and migration have challenged school staff members' ways of working. This study aimed to identify the challenges faced by Finnish school staff in supporting students with migrant backgrounds, and to elaborate on how they enact professional agency toward these challenges. The data consist of 15 thematic interviews with staff members across various work positions in two Finnish lower secondary schools. Based on thematic analysis, the challenges within the staff community and the education policies were found to include the following: (1) the diversification of students makes tensions more visible in the staff community, and (2) inflexible education policies restrict support processes. In these challenges, staff members practiced professional agency via a focus on their own work level, relying on certain colleagues, and trusting their own professionalism, under strong autonomy tradition. However, outside of their own work level, staff members prefer to adapt to the conditions by compromising, and they seem have not strong participation in higher decision-making. As a conclusion, it would be valuable to resource time expressly for establishing new practices, strengthen head teachers' ability to promote a culture of shared leadership, while clarifying the boundaries of pedagogical autonomy, and facilitate the participation in higher decision-making.